PREVALENCE OF DIABETIC RETINOPATHY IN PATIENT TYPE 2 DIABETES MELLITUS AT INTERNAL MEDICINE POLICLINIC SANGLAH HOSPITAL - Ni Made Sintia Anggia Sari; Made Ratna Saraswati (Universitas Udayana, 2013)
One of the complications that can occur in microvaskular diabetes mellitus is diabetic retinopathy. This research was carried out to know the prevalence of diabetic retinopathy in patients type 2 diabetes mellitus at internal divison of Sanglah Hospital. The method used is cross sectional by collecting data from the questionnaire and secondary data of medical record patient's type 2 DM. On this research acquired 111 patients (35.1%) with diabetic retinopathy and (64,9%) nonretinopathy. In the group with good level of HbA1c (<6.5%) the prevalence of diabetic retinopathy obtained 53.2%, in the group of patients with moderate level of HbA1c (6.5-8%) as much as 22.5%, and in the group of patients with HbA1c bad level (>8%) as much as 24.3%. The prevalence of the occurrence of DM complications in the diabetic retinopathy is still high, and a good level of HbA1c does not guarantee a person can’t have complication because the complication can also happens are affected by hypertension, dyslipidemia, age, and duration of DM.